2021
DOI: 10.3389/fmed.2021.706407
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Significance and Prognostic Roles of Indirect Bilirubin/Albumin Ratio in Hepatic Encephalopathy

Abstract: Background and Aim: Hepatic encephalopathy (HE) is a neurological disease caused by severe liver disease. Early identification of the risk factor is beneficial to the prevention and treatment of HE. Free bilirubin has always been considered to be the culprit of neonatal kernicterus, but there is no research to explore its role in HE. In this study, we aim to study the clinical significance of the indirect bilirubin-albumin ratio in HE.Methods: A retrospective case-control study of 204 patients with liver failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…65,66 While the link between biliverdin and HE has not been explicitly elucidated, previous studies have described a strong relationship between HE and free bilirubin. 6769 Interestingly, free bilirubin is rapidly solubilized by bile acids in vitro , perhaps explaining the potential protective effects of bile acids observed in our study In the context of bilirubin metabolism, our FBMN data suggest that an increase in the chemical reduction of biliverdin is involved in the development of post-TIPS HE ( Fig. 5g) .…”
Section: Discussionmentioning
confidence: 55%
“…65,66 While the link between biliverdin and HE has not been explicitly elucidated, previous studies have described a strong relationship between HE and free bilirubin. 6769 Interestingly, free bilirubin is rapidly solubilized by bile acids in vitro , perhaps explaining the potential protective effects of bile acids observed in our study In the context of bilirubin metabolism, our FBMN data suggest that an increase in the chemical reduction of biliverdin is involved in the development of post-TIPS HE ( Fig. 5g) .…”
Section: Discussionmentioning
confidence: 55%
“…Previous clinical and basic studies have found that free bilirubin in serum is an important cause of kernicterus in neonates and adults (4,5,23,24). Recently, a retrospective case-control study showed that the indirect bilirubin-albumin ratio is an independent factor of hepatic encephalopathy in patients with liver failure (aOR:1.63, 95% CI: 1.32~2.00, p < 0.001) (25). Our finding that DB/TB is negatively correlated to cerebral score for hepatic encephalopathy (aOR: 0.01, 95% CI: 0.00~0.86, p = 0.043) is in accordance with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that DB/TB is negatively correlated to cerebral score for hepatic encephalopathy (aOR: 0.01, 95% CI: 0.00~0.86, p = 0.043) is in accordance with these results. Notably, the administration of albumin or by pharmacological inhibition of indirect bilirubin production in a genetic model of hyperbilirubinemia could improve neurodevelopment and reduce apoptosis of cerebral cells remarkably (25,26). Similarly, promoting the conversion of indirect bilirubin to direct bilirubin was shown as beneficial in two patients with Crigler-Najjar syndrome type II who developed kernicterus in adulthood (24).…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin neurotoxicity is caused by a high level of unbound unconjugated bilirubin that is unbound to albumin since albumin‐bound bilirubin probably does not cross an intact blood–brain barrier 21,22,24 . Although there is no research on unbound unconjugated bilirubin in ALF to the best of our knowledge, Lin et al 25 reported that the unconjugated bilirubin‐albumin ratio constitutes the most powerful risk factor in the occurrence of HE in adult ALF. In this study, peak serum bilirubin level was significantly higher in patients with NI.…”
Section: Discussionmentioning
confidence: 99%